Euchaetomera plebeja Hansen, 1912 (Mysida; Mysidae) in western Mexico - Hernández-Payán, J.c.; Hendrickx, M.e. (Zootaxa, 2024)
The opossum shrimp Euchaetomera plebeja Hansen, 1912 (Mysida; Mysidae) is one of the nine described species currently known in this genus. Until now, it has been considered a rare species, only partly illustrated, known from western Mexico, western Colombia, Peru, and Chile (one specimen in each locality), with a possible additional record off Hawaii. In a recent study, it was recorded abundantly in western Mexico where it was collected in 20 localities, all in the Gulf of California. A total of 109 specimens were collected with mid water nets in oblique samples taken between surface and 1600 m depth, including 35 males and 74 females. Based on this new and abundant material, E. plebeja is fully described and illustrated.